Evaluation of Spawning- and Natal-Site Fidelity of Larimichthys polyactis in the Southern Yellow Sea Using Otolith Microchemistry - Song, Dade; Xiong, Ying; Jiang, Tao; Yang, Jian; Zhong, Xiaming; Tang, Jianhua; Kang, Zhongjie (Frontiers in Marine Science, 2022)
Small yellow croaker Larimichthys polyactis is an important commercial fish species; however, industrial-scale fishing has largely contributed to the changes in its biological characteristics, such as individual miniaturization, faster growth, and younger average age. Robust understanding of the pivotal life history of L. polyactis, a typical oceanodromous species, is needed for its conservation and restoration. However, L. polyactis fidelity to natal or spawning sites is not well understood and, at present, there is no effective management strategy to guarantee the sustainable exploitation of L. polyactis. This study used laser ablation inductively coupled plasma-mass spectrometry to analyse the elemental composition of otoliths from 60 adult yellow croakers caught in the southern Yellow Sea, including two spawning groups with 1- and 2-year-old fish (S1 and S2, respectively) sampled close to China and one overwintering group including two-year-old fish (O2) sampled close to South Korea. The ratios of elements (Li, Na, Sr, and Ba) to Ca in the otolith core zones were significantly higher (P < 0.05) than in those of the year one (Y1) and year two (Y2) annual rings, but there were no significant differences in the elemental ratios between the Y1 and Y2 zones. Principal component analysis (PCA) of the elemental otolith signatures of the core, Y1, and Y2 zones in the three groups revealed two distinct clusters (cluster 1: S1-core, S2-core, and O2-core zones; cluster 2: S2–Y1, O2–Y1, S2–Y2, and O2–Y2 zones) and one zone (S1–Y1), suggesting spawning-site fidelity and natal-site fidelity uncertainty, especially considering the dispersal by current in prolonged period (50 h) from fertilized eggs to hatching and internal effect, such as yolk sac and maternal effect. Furthermore, these results indicated that the S2 and O2 groups could represent the same population, suggesting a stable migratory route for L. polyactis in Chinese and South Korean waters, whereas the S1 group could represent another population. This suggests the possibility a mixed L. polyactis population in the southern Yellow Sea. Characterization L. polyactis spawning-site fidelity is a crucial step toward linking spawning-site fidelity of this overexploited species with thorough conservation and management strategies.